Regulation of WNT Signaling by VSX2 During Optic Vesicle Patterning in Human Induced Pluripotent Stem Cells. (5th July 2016) - Capowski, Elizabeth E.; Wright, Lynda S.; Liang, Kun; Phillips, M. Joseph; Wallace, Kyle; Petelinsek, Anna; Hagstrom, Anna; Pinilla, Isabel; Borys, Katarzyna; Lien, Jessica; Min, Jee Hong; Keles, Sunduz; et al.
Abstract: Few gene targets of Visual System Homeobox 2 (VSX2) have been identified despite its broad and critical role in the maintenance of neural retina (NR) fate during early retinogenesis. We performed VSX2 ChIP-seq and ChIP-PCR assays on early stage optic vesicle-like structures (OVs) derived from human iPS cells (hiPSCs), which highlighted WNT pathway genes as direct regulatory targets of VSX2. Examination of early NR patterning in hiPSC-OVs from a patient with a functional null mutation in VSX2 revealed mis-expression and upregulation of WNT pathway components and retinal pigmented epithelium (RPE) markers in comparison to control hiPSC-OVs. Furthermore, pharmacological inhibition of WNT signaling rescued the early mutant phenotype, whereas augmentation of WNT signaling in control hiPSC-OVs phenocopied the mutant. These findings reveal an important role for VSX2 as a regulator of WNT signaling and suggest that VSX2 may act to maintain NR identity at the expense of RPE in part by direct repression of WNT pathway constituents. Abstract : Visual systems homeobox 2 (VSX2) is a key transcription factor involved in neural retinal development. However, surprisingly few gene regulatory targets are known for VSX2 beyond Microphthalmia induced transcription factor (MITF), a protein involved in the development of retinal pigmented epithelium (RPE). We used patient-specific human pluripotent stem cells carrying a mutation in VSX2 that abolishes DNA binding activity (R200Q), combined with pharmacological manipulations and chromatin immunoprecipitation, to demonstrate a novel interaction between VSX2 and WNT signaling genes. In VSX2 R200Q cultures, VSX2 binding to WNT signaling genes is abolished and optic vesicle cells aberrantly adopt an RPE fate in lieu of neural retina. This effect that can be partially overcome by inhibition of WNT signaling, or induced in wild type cells through promotion of WNT signaling. This study also presents the first unbiased list of VSX2 targets, thus providing a resource for identification of other genes and mechanisms involved in this biological process.